Pengembangan Desain Pembelajaran Menggunakan Model Pembelajaran Discovery Learning Berbasis Hots - Sriharyanti, Riska; Loliyana, Riswandi (Jurnal Pendidikan Progresif, 2017)
The aim of this study research development are to review analyze: 1). The scool’s condition and potential, 2). Learning process and 3). Measure the effectif, efficiency and attractivity, the using methode is HOTS design Based discovery learning. The used methods is Research & Development (R & D). The population is all fifth grade students of SD Negeri 2 Labuhan Ratu. Samples were students of class VA and VB SD Negeri 2 Labuhan Ratu. Data collection techniques are observation, questionnaires and tests.  Keyword: Discovery Learning, Higher Order Thinking Skill, Learning DesignDOI: http://dx.doi.org/10.23960/jpp.v7.i2.201701